Global Adaptation and Resilience to Climate Change - Zolnikov, Tara Rava (Palgrave Studies in Climate Resilient Societies, 2019)
'Global Adaptation and Resilience to Climate Change' provides an intriguing and accessible glimpse into how different regions around the world cope with the growing environmental burdens in which global changes in climate may contribute. This book provides a comprehensive overview for readers who may wish to dig deeper into the human toll of an unstable world." - J.Y.Y. Wong, Published author in Environment International, Occupational and Environmental Medicine, Cancer Research "Global Adaptation and Resilience to Climate Change sheds an important light on climate change and the impacts that various countries are experiencing around the world. Through this text, one gains an understanding of some of the key policies and adaptation strategies currently being employed to reduce greenhouse gas emissions globally, thus offering a useful educational tool on such matters." - Shahir Masri, author of 'Beyond Debate: Answersto 50 Misconceptions on Climate Change' This book explores the link between climate change and resiliency on each continent of the world. It reviews how climate change affects populations, not only through environmental exposures and health outcomes, but how people live their lives. Zolnikov brings together a set of experts to offer a novel perspective on understanding climate change vulnerability alongside adaption measures being implemented. Each chapter includes an overview on how climate change will affect that continent alongside current adaptation, mitigation, and policies that seek to improve population outcomes. As a whole, the book explores why a "one size fits all" approach to promote climate change resiliency does not work; however, a global perspective can facilitate people learning from one another and facing climate change together. Tara Rava Zolnikov is an associate professor in the Schoolof Health and Human Services at National University, USA. Her research primarily focuses on global health issues in low- and middle-income countries. She has worked internationally on a variety of public health projects, ranging from infectious diseases to climate change. She is a qualitative researcher and concentrates on providing vulnerable populations with a voice.